2004
DOI: 10.1007/s00359-003-0484-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for detection and discrimination of pheromonal bile acids by the olfactory epithelium of female sea lampreys ( Petromyzon marinus )

Abstract: Electro-olfactograms were used to determine sensitivity and specificity of olfactory organs of female sea lampreys ( Petromyzon marinus) to four bile acids: 3-keto petromyzonol sulfate and 3-keto allocholic acid from spermiating males and petromyzonol sulfate and allocholic acid from larvae. Spermiating male bile acids are thought to function as a mating pheromone and larval bile acids as a migratory pheromone. The response threshold was 10(-12) mol l(-1) for 3-keto petromyzonol sulfate and 10(-10) mol l(-1) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
59
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 11 publications
7
59
0
Order By: Relevance
“…During spawning migration, sea lampreys encounter a mixture of bile acid steroids released from larval sea lamprey in the streambed, and these larval odours have an important role in identifying a suitable river for spawning and larval rearing (Li et al, 1995;Sorensen and Vrieze, 2003). Once a spawning location is found, spermiated male sea lampreys release steroid pheromones, which induce movement/searching and spawning behaviours in ovulated female sea lamprey (Li et al, 2002;Siefkes et al, 2003;Siefkes and Li, 2004;Johnson et al, 2005Johnson et al, , 2009. Physiological studies have also investigated olfactory function in the sea lamprey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During spawning migration, sea lampreys encounter a mixture of bile acid steroids released from larval sea lamprey in the streambed, and these larval odours have an important role in identifying a suitable river for spawning and larval rearing (Li et al, 1995;Sorensen and Vrieze, 2003). Once a spawning location is found, spermiated male sea lampreys release steroid pheromones, which induce movement/searching and spawning behaviours in ovulated female sea lamprey (Li et al, 2002;Siefkes et al, 2003;Siefkes and Li, 2004;Johnson et al, 2005Johnson et al, , 2009. Physiological studies have also investigated olfactory function in the sea lamprey.…”
Section: Introductionmentioning
confidence: 99%
“…Basic amino acids and a variety of steroid bile acids (including the lamprey pheromones) stimulate olfactory sensory responses from the main olfactory epithelium (e.g. Li et al, 1995Li et al, , 2002Li and Sorensen, 1997;Siefkes and Li, 2004;Sorensen et al, 2005;Johnson et al, 2009). However, the peripheral olfactory organ also houses abundant tubular diverticula known as the accessory olfactory organ (Hagelin and Johnels, 1955).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that bile acid profiles of lake trout (Salvelinus namaycush) are largely influenced by sex and maturation stage (Zhang et al, 2001) and that bile of female Rainbow trout (Oncorhynchus mykiss) contains a pheromone (Vermeirssen & Scott, 2001). Moreover, malespecific bile acids of sea lamprey (Petromyzon marinus) are potent and specific stimulants to the female olfactory organ (Siefkes & Li, 2004). Furthermore, electrophysiological studies demonstrated that an odotopic map of responses to bile acids and amino acids are represented in different regions of olfactory bulbs of chars (Salvelinus alpinus) and graylings (Thymallus thymallys) (Doving et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Many species of fish have been shown to have an acute olfactory sensitivity to bile salts (Døving et al, 1980;Siefkes and Li, 2004;Zhang et al, 2001). Although the biological function of this phenomenon is unclear, with the notable exception of the sea lamprey Petromyzon marinus (Li et al, 2002;Polkinghorne et al, 2001;Sorensen et al, 2005), the stability and water solubility of the bile salt molecule makes it an ideal candidate for a role in chemical communication (Rosenthal and Lobel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, behavioural evidence has shown that prey fish are able to recognise potential predators by olfaction (Kristensen and Closs, 2004;Rosenthal and Lobel, 2006). Furthermore, migration could involve olfactory detection of bile salts (Siefkes and Li, 2004).…”
Section: Introductionmentioning
confidence: 99%